A three-dimensional analysis of the volleyball one-foot jump spike - Huang, C. F.; Liu, Ch. Ch.; Shu, T. Y. (coachesinfo.com, 1998)
The purpose of this study was to describe the biomechanical characteristics of the one-foot jump spike performed by elite female players. It was noted that female one-foot jump spikers had a smaller ball velocity and lower jumped height than male two-foot jump spikers. In addition, the female one-foot jump spikers had a greater approach body angle and a smaller approach net angle than the male two-foot jump spikers; they also had a wider view and maximize the hitting area during the spike action.